The teaching crisis in less developed countries - Marcenaro-Gutiérrez, Óscar David; López-Agudo, Luis Alejandro (My University, 2018)
There is a huge concern on the influence of teachers on students’ cognitive learning. However, little is known about the causal impact of teachers’ knowledge on students’ performance. In addition, this effect is likely to change depending on the group of countries and regions under analysis. In the current research, we propose to study this subject for sixth grade teachers and, concretely, for less developed regions. To achieve this aim, we have employed the heterogeneity within-student between-subjects of teachers’ subject knowledge on students’ academic achievement. We have found that, for the countries under analysis, teachers’ subject knowledge does not have a significant influence on students’ academic achievement; many robustness checks have supported this result. This could be indicating that, in these countries, teachers do not have enough knowledge to teach students, what brings some policy implications.
Keywords: Rendimiento académico - Países en desarrollo; Less developed regions; Students’ academic achievement; Teachers’ subject knowledge